Pengaruh Diaphragmatic Breathing Exercise terhadap Fungsi Pernapasan (RR dan APE) pada Lansia di UPT PSLU Kabupaten Jember (The Effect of Diaphragmatic Breathing Exercise on Respiration Function (RR and PEFR) in Elderly at UPT PSLU Jember Regency) - Santi Dwi Pangestuti; Murtaqib Murtaqib; Nur Widayati (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Oxygenation is human major basic need for maintaining body cell metabolism, survival and activities of various body organs. Respiratory system and cardiovascular system change throughout the aging process. Decreased respiratory function will affect the fulfillment of the needs of oxygenation in the elderly. Diaphragmatic breathing exercise is one of methods to maintain and improve respiratory functions in the elderly. This research aimed to determine the effect of diaphragmatic breathing exercise on respiratory functions (RR and PEFR) in the elderly. This research is a pre-experimental research with one group pretest and posttest design. Sampling technique used purposive sampling with 14 elderly given intervention of diaphragmatic breathing exercise once a day for 14 days. The collection of data was by observation, that is, by measuring the value of RR and APE before and after diaphragmatic breathing exercise. Data analysis used dependent t-test with α=5%. The research results of statistical calculation indicated p value of 0.000 (p